The interplay between food market access and farm household dietary diversity in low and middle income countries: A systematic review of literature - Nandi, R.; Nedumaran, S.; Ravula, P. (Elsevier, 2021)
A significant share of undernourished people are smallholder farmers in low and middle-income countries. Recent studies advocate improving market access as an important pathway towards improving the dietary diversity of farm households over increasing farm production diversity. A systematic review of five databases using Priori criteria identified 28 original studies from 14 low and middle income countries by screening 786 articles using different indicators of market access, diets, and nutrition. Most of the studies reported a consistent positive association between access to markets and dietary diversity, and few studies reported positive or negative association. However, findings are context-specific from several countries in Africa and Asia. Further research is needed to conclude that improving market access is an effective pathway to improve a farm household's dietary quality. Eight research priorities are identified based on the gaps in the existing research literature.